Dose Sculpting Intensity Modulated Radiation Therapy for Vertebral Body Sparing in Children With Neuroblastoma - Ng, Lydia W.; Wong, Kenneth K.; Ally Wu, Chia-Ling; Sposto, Richard; Olch, Arthur J. (International journal of radiation oncology, biology, physics, 2018)
To assess the effect of dose sculpting intensity modulated radiation therapy on vertebral body growth in children with neuroblastoma. From 2000 to 2011, 88 children with neuroblastoma underwent radiation at the authors' institution. Children with paravertebral tumors with at least 3 years of evaluable posttreatment imaging were included, and children who underwent spine reirradiation before follow-up were excluded. If vertebral bodies could not be spared, these “target” vertebral bodies were treated to at least 18 Gy. Thoracic and lumbar vertebral bodies were assessed separately. Dose data for target, spared, and internal control vertebral bodies were extracted. Multivariate generalized estimating equation modeling was used to assess the effect of dose and other clinical factors on vertebral body growth. A total of 34 patients (20 boys, 14 girls) met study criteria. Median age at start of radiation was 4.3 years; all but 1 had prior high-dose chemotherapy with stem cell rescue. Mean growth rates of target, spared, and control vertebral bodies (cm/body/y) were, respectively, 0.027, 0.032, and 0.044 in thoracic spine and 0.033, 0.055, and 0.083 in lumbar spine. On multivariate generalized estimating equation analysis, higher dose, older treatment age, male gender, and thoracic spine location were significantly associated with decreased vertebral body growth (P<.0001, P<.0001, P=.007, and P<.0001, respectively). Dose and spine location were significant in a 3-way interaction model (P<.0001). Vertebral bodies spared by intensity modulated radiation therapy grew faster than target vertebrae. Regardless of intent to spare or target, multivariate analysis confirms that lower dose results in significantly increased growth rate. This technique should be investigated prospectively.